A cutting force predicting model in orthogonal machining of unidirectional CFRP for entire range of fiber orientation. Issue 1 (March 2017) - Chen, Liangxi; Zhang, Kaifu; Cheng, Hui; Qi, Zhenchao; Meng, Qingxun
Abstract Cutting force prediction of orthogonal cutting unidirectional carbon fiber-reinforced plastic (UD-CFRP) is crucial in the reduction of machining defects. This paper aims to construct a force prediction model for orthogonal cutting of UD-CFRP using beams on elastic foundation theory and the minimum potential energy principle (MPEP) when fiber orientation (θ ) varies from 0° to 180°. Models for different fiber orientation ranges were established separately, i.e., (1) 0°< θ  < 90°, (2) 90°≤ θ  < 180°, and (3) 0°. The deformation of the fibers was considered as a bending problem of a beam on elastic foundation. Total cutting force was composed of cutting forces from rake face, tool edge, and relief face of the cutting tool. As 0°< θ  < 90°, Vlazov's elastic foundation was introduced to calculate pressing forces between cutting tool edge and the representative volume element (RVE). The force applied on rake face was the integral value of resistant forces from those micro-elements of the curved chip based on well-established shear angle-cutting force relationships in Piispanen's card model. When 90°≤ θ  < 180°, non-uniform Winkler foundation was applied to calculate force between rake face and the RVE. Whenθ  = 0°, the energy equation of the splitting process was constructed by using virtual crack close technique, and plugging force between rake face and the chip was derived from the equation. This mechanical model reveals mapping relationships between cutting forces and key variables such as the fiber orientation, rake angle, depth of cut, and so on. Corresponding experiments were conducted, and predictions were in acceptable agreement with the experimental measurements.